THE INFLUENCE OF FINANCIAL LITERACY, LIFESTYLE, SELF-CONTROL, AND PEER CONFORMITY ON STUDENT’S CONSUMPTIVE BEHAVIOR - Febriana Hidayanti; Naelati Tubastuvi; Wida Purwidianti; Hermin Endratno (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to analyze the effect of financial literacy, lifestyle, self-control, and peer conformity on the consumption behavior of students. The population is FEB students at Universitas Muhammadiyah Purwokerto, Universitas Jenderal Soedirman, and Universitas Islam Negeri KH. Saifuddin Zuhri Purwokerto class of 2019-2021, which have a total of 4.341 students. The sample for this study is 100 students. This study used a purposive sampling technique to collect the data. Then it was processed using SPSS version 26 with the analytical tools were validity test, reliability test, coefficient of determination test, multiple linear regression, and t-test. The result of this study indicates that 1) financial literacy had no significant effect on student consumptive behavior, 2) lifestyle had a positive and significant effect on student consumptive behavior, 3) self-control had no significant effect on student consumptive behavior, 4) peer conformity had a positive and significant effect on student consumptive behavior.